Mansonella ozzardi (Filaria tucumana) in the Argentine Republic. Review and preliminary survey in the Province of Salta (Colombia Medica, 1981)
Following a review of the Argentine literature on Mansonella ozzardi a survey for microfilariae of this filarid is reported. Three hundred and forty males, 18 to 24 years of age (almost o.6% of the total male population in that age group in the Province of Salta, Argentina), were investigated. One ml of blood was examined, following concentration according to Knott's technique. Despite the fact that one-third of the individuals examined came from the eastern region of the province, where endemic areas had been described, none was infected. The negative results could be due to the small number of persons examined from the transmission areas or to the interruption of M. ozzardi transmission. The search for the "microfilaria tucumana" will continue in specific areas of Salta, Jujuy and Tucumán as well as in homes for the elderly in Salta City.